MAQĀṢIDAL-SYARĪ’AH DALAM KAJIAN TEORI EKONOMI ABU ISḤĀQ Al-SYĀṬIBĪ - fasya fasya (IAIN Langsa, 2017)
Al-Syāṭibi offered a concept its called maqāṣid ash-shari'a. The purpose of this concept is protecting human rights maslahat. It can be realize if five prime unsures of live protected and implementated, they are religion, soul, rasionality, chilhood and property. Maqāṣid ash-shari'a contains of three grades, they are ḍarūriat, ḥajiyat and taḥsiniyat. Ḥajiyat completed ḍarūriat, taḥsiniyat completedḥajiyat grade thoght ḍarūriat is the base of ḥajiyat and taḥsiniyat. So far, he explained thats all activity or all secundary orientations must be ignore even there are high purpose in the world (ḍarūriyat and ḥajiyat).